2001
DOI: 10.1161/01.hyp.37.2.619
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid B Receptor–Mediated Responses in the Nucleus Tractus Solitarius Are Altered in Acute and Chronic Hypertension

Abstract: Abstract-The increase in mean arterial pressure evoked by injection of the ␥-aminobutyric acid (GABA) B agonist baclofen into the nucleus tractus solitarius (NTS) is greater in spontaneously hypertensive rats and renal wrap chronically hypertensive (CHT) rats compared with normotensive (NT) controls. We report here that the baclofeninduced pressor response (BIPR) is enhanced after acute hypertension (AHT) of only 30 minutes. Sprague-Dawley rats were anesthetized with Inactin, paralyzed, and artificially ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 14 publications
3
35
0
1
Order By: Relevance
“…Increased nociceptive afferent inputs from the hindlimb increased the expression of the GABA B mRNA in dorsal root ganglia and dorsal regions of the lumbar spinal cord (9), suggesting that synaptic activity can regulate the expression of GABA B receptors. We have reported that HT is associated with an increased expression of GABA B receptor mRNA (3) and provided indirect evidence that this change occurs primarily in postsynaptic, as opposed to presynaptic, elements of the NTS (17). This suggests an enhanced expression of GABA B receptors, and our data further suggest that this expression occurs in MSNs.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Increased nociceptive afferent inputs from the hindlimb increased the expression of the GABA B mRNA in dorsal root ganglia and dorsal regions of the lumbar spinal cord (9), suggesting that synaptic activity can regulate the expression of GABA B receptors. We have reported that HT is associated with an increased expression of GABA B receptor mRNA (3) and provided indirect evidence that this change occurs primarily in postsynaptic, as opposed to presynaptic, elements of the NTS (17). This suggests an enhanced expression of GABA B receptors, and our data further suggest that this expression occurs in MSNs.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have demonstrated enhanced responses to NTS microinjection of the GABA B receptor agonist baclofen in this (3,17) and other (15) models of HT. This finding is consistent with the enhanced inhibition of monosynaptic AN-evoked discharge in NTS neurons by iontophoretic application of baclofen.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The Woodchuck posttranscriptional regulatory element (WPRE) and the presence of a bovine growth hormone polyadenylation sequence ensure high transcription following transduction. Microinjections were performed in an aseptic environment as described previously (10,29) to inject shRNA and scRNA into the NTS of WKY rats under 2% isoflurane anesthesia. To cover the rostralcaudal extent of NTS HSD2 neurons, three injections of the viral construct (100 nl; Ͼ1 ϫ 10 12 genomic particles/ml) were injected 0.5 mm below the surface at calamus scriptorius and bilaterally at 0.5 mm rostral and 0.5 mm lateral to calamus.…”
Section: Methodsmentioning
confidence: 99%
“…Other pathways include the cardiopulmonary reflex and blood volume regulation, which also display evidence of a chronic effect on SNA (87,93). In addition, chronic alterations within the central pathways themselves may also regulate the long-term level of SNA (43,59,94).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%